Analysis of the airway transport model and its economic impact in the Duran canton in 2021 - Ascencio, Karina (2026)
This research examines the transportation mobility issues faced by citizens of Durán who have benefited from the construction of the cable car system. The objective of the study is to determine the socioeconomic impact of the cable car transportation system in the Durán canton in 2021. This research follows a non-experimental design, based on documentary review and a quantitative approach. A questionnaire was used as a research technique, targeting a sample of 384 passengers who frequently travel to Durán. The research results indicate that prior to the implementation of the cable car transportation system, the socioeconomic reality of the residents of Durán exhibited low employment levels, high informality, and low purchasing power. Unfortunately, this differed from the image that was promoted to potential users of the system, as it shifted from being a daily means of transportation to becoming an attractive tourist attraction offering scenic views of the river landscape connecting Guayaquil and Durán. Ultimately, based on the findings, it is concluded that the majority of residents do not perceive significant changes in the economy of the Durán canton as a result of the cable car implementation, leading to a low level of satisfaction regarding this matter.